1983
DOI: 10.1177/00220345830620121201
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature Behavior of a Pd-Ag Alloy for Porcelain

Abstract: The mechanism of formation of nodular material on the surface of a Pd-Ag-based alloy for porcelain during pre-porcelainization heat treatment was investigated using scanning electron microscopy, x-ray diffraction, quantitative metallography, and Auger electron spectroscopy. The nodules were found to form by a Nabarro-Herring creep mechanism driven by the internal oxidation of tin and indium. Implications of this process with regard to porcelain bonding and discoloration are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 23 publications
5
42
0
2
Order By: Relevance
“…Before reduction, it appeared as if some of the surface was covered with a thin layer and, where this had peeled off, a few intergranular cracks could be seen and nodules of pure Pd were detected and verified by EDAX. Such nodules are apparent for internally oxidized Pd-Al alloys [5] which is consistent with the occurrence of internal oxidation [3]. Extensive and large intergranular cracks were apparent after reduction as seen in Figure 1.…”
Section: Optical Microscopic Observations Sem Edax Sanssupporting
confidence: 79%
“…Before reduction, it appeared as if some of the surface was covered with a thin layer and, where this had peeled off, a few intergranular cracks could be seen and nodules of pure Pd were detected and verified by EDAX. Such nodules are apparent for internally oxidized Pd-Al alloys [5] which is consistent with the occurrence of internal oxidation [3]. Extensive and large intergranular cracks were apparent after reduction as seen in Figure 1.…”
Section: Optical Microscopic Observations Sem Edax Sanssupporting
confidence: 79%
“…It may be observed that the relationship between time for full oxidation and (1/milling time) 2 is followed linear law. This result is coincident with Equation (12). So the experimental result (Fig.…”
Section: Effect Of Ball-milling On Full Oxidation Time Of Ag-zn Alloysupporting
confidence: 87%
“…The formation of spheric Ag on the surface may be attributed to the external diffusion of silver. Mackert et al [12] studied the internal oxidation dynamics and microstructure of Ag-In alloy. They found that the formation of pure silver on the surface is due to external diffusion of silver.…”
Section: The Effect Of Ball-milling On Oxidation Kineticsmentioning
confidence: 99%
“…Noble alloys for bonding to dental porcelain contain small amounts of secondary elements, such as tin, indium and iron, which form the native oxide and also increase the alloy strength. However, Mackert et al [9] found that during initial oxidation heat treatment, metallic Pd-Ag nodules formed on the surface of a palladium-silver alloy for metal-ceramic restorations and only internal oxidation occurred for the tin and indium present in the alloy composition. They concluded that porcelain bonding arose predominantly from mechanical interlocking with the nodules.…”
Section: Alloys For Fixed Prosthodontics (Metal-ceramic Restorations)mentioning
confidence: 99%